Reservoirs of Non-baumannii Acinetobacter Species - Al Atrouni, Ahmad; Joly-Guillou, Marie-Laure; Hamze, Monzer; Kempf, Marie (Frontiers in Microbiology, 2016)
Acinetobacter spp are ubiquitous gram negative and non fermenting coccobacilli that have the ability to occupy several ecological niches including environment, animals and human. Among the different species, Acinetobacter baumannii has evolved as global pathogen causing wide range of infection. Since the implementation of molecular techniques, the habitat and the role of non baumannii Acinetobacter in human infection have been elucidated. In addition, several new species have been described. In the present review, we summarize the recent data about the natural reservoir of non-baumannii Acinetobacter including the novel species that have been described for the first time from environmental sources and reported during the last years.